Associations Between Gross Motor Coordination and Executive Functions: Considering the Sex Difference in Chinese Middle-Aged School Children - Liu, Shijie; Chen, Si-Tong; Cai, Yujun (Frontiers in Psychology, 2022)
Abstract: Considering that motor and cognitive processes are intertwined and inhibit or help each other throughout life and that primary school age is one of the most critical stages of children’s cognitive and motor development, this study aimed to investigate the relationship between executive functions and gross motor skills in Chinese children aged 9-10 years, as well as gender differences. The flanker task, the 1-back task, the more-odd shifting task, and the test of gross motor coordination (KTK) were used to collect data on executive functions and gross motor coordination. The results showed the following: First, there was a weak association between gross motor coordination and the inhibition reaction time in the congruent test and the reaction time of working memory(r= -0.181 ~ -0.233), but no association was found between gross motor coordination and cognitive flexibility. Second, a weak to moderate correlation was presented between the move sideways test and the inhibition reaction time in the congruent test and the reaction time in the refreshing test of the working memory (r= -0.211 ~ -0.330). Finally, gender influenced on the relationship between gross motor coordination and the reaction time of both inhibition (βGender= -.153, p<0.05) and working memory (βGender= -.345, p<0.01). To conclude, our results suggest that children with better motor coordination skills require less reaction time, especially girls, and this association was more substantial than in boys. The finding supports the current assertion that there are commonalities between gross motor coordination and cognitive control by showing the relationship between gross motor coordination and complex cognitive processes (executive function) in pre-adolescent children.